Role of MSC‐derived small extracellular vesicles in tissue repair and regeneration - Aguiar Koga, Bruna Andrade; Fernandes, Letícia Alves; Fratini, Paula; Sogayar, Mari Cleide; Carreira, Ana Claudia Oliveira (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stem cells (MSCs) are crucial for tissue homeostasis and repair, secreting vesicles to the extracellular environment. Isolated exosomes were shown to affect angiogenesis, immunomodulation and tissue regeneration. Numerous efforts have been dedicated to describe the mechanism of action of these extracellular vesicles (EVs) and guarantee their safety, since the final aim is their therapeutic application in the clinic. The major advantage of applying MSC-derived EVs is their low or inexistent immunogenicity, prompting their use as drug delivery or therapeutic agents, as well as wound healing, different cancer types, and inflammatory processes in the neurological and cardiovascular systems. MSC-derived EVs display no vascular obstruction effects or apparent adverse effects. Their nano-size ensures their passage through the blood–brain barrier, demonstrating no cytotoxic or immunogenic effects. Several in vitro tests have been conducted with EVs obtained from different sources to understand their biology, molecular content, signaling pathways, and mechanisms of action. Application of EVs to human therapies has recently become a reality, with clinical trials being conducted to treat Alzheimer’s disease, retina degeneration, and COVID-19 patients. Herein, we describe and compare the different extracellular vesicles isolation methods and therapeutic applications regarding the tissue repair and regeneration process, presenting the latest clinical trial reports.